Violence, images and memory in the New Coronavirus and good government. Memories of the Covid-19 pandemic in Peru by Edilberto Jiménez - Cabel García, Andrea (2022)
This article analyzes a group of images and testimonies compiled in Nuevo coronavirus y buen gobierno. Memorias de la pandemia de COVID-19 en Perú by the Ayacucho artist and anthropologist Edilberto Jiménez based on three axes: the representations of the virus in the popular imagination, the subjective and objective violence of the virus as captured in the drawings, and the construction of civil society agency in the face of this violence. We argue that this book embodies a restorative justice as well as a polyphonic testimony of how the pandemic made visible and accentuated the differences as inequalities in the most vulnerable citizens: women, children, elderly people from the poorest families of San Juan de Lurigancho, one of the districts with the highest extreme poverty in Lima. Thus, we underline the politicaltestimonial function of the book, the same one that aims at the creation of a memory about the health crisis. With all this, we conclude that Jiménez’s book is a necessary contribution to re-understand the diverse effects of the pandemic in the areas of extreme poverty in Peru and also to reflect on the role of images to build a memory in which the protagonists are the most affected.